PROFIL HERPES ZOSTER DI POLIKLINIK KULIT DAN KELAMIN RSUP PROF. DR. R. D. KANDOU MANADO 2011-2013 - Danardono, Dwi H.; Niode, Nurdjannah J. (Jurnal Biomedik : JBM, 2015)
Abstract: Herpes zoster is a reactivation of varicella zoster virus (VZV) that affects the skin and mucosa. The incidence of herpes zoster increases with age. There are three main goals of treatment: overcoming the acute viral infection, relief from acute pain, and prevention of post-herpetic neuralgia. This study aimed to determine the profile of herpes zoster in the Dermatology Clinic of Prof. Dr. R. D. Kandou General Hospital for three years based on the number of new cases, gender, ages, dermatome locations, and treatment. This was a retrospective study using the medical records of the Dermatology Clinic of Prof. Dr. R. D. Kandou General Hospital during period January 2011- Desember 2013. The results showed that there were 96 (0.84%) herpes zoster patients of 11,367 new patients, consisted of 51 (53.11%) males and 45 (46.87%) females. The most frequent age group was 45-64 years with a number of 59 cases (61.46%). The most frequent dermatome location was on the left thoracic region with a number of 18 cases (18.75%). The most widely prescribed treatment was a combination of antiviral agent, analgesic drugs, roborantia, and topical medicine (powder/antibiotic cream), with a number of 43 cases (44.79%).Keywords: herpes zoster, morbidityAbstrak: Herpes zoster merupakan reaktivasi virus varicella zoster (VZV) yang menyerang kulit dan mukosa. Insiden herpes zoster meningkat seiring dengan bertambahnya usia. Terdapat tiga tujuan utama pengobatan yaitu: mengatasi infeksi virus akut, mengatasi nyeri akut, dan mencegah timbulnya neuralgia pasca-herpetik. Penelitian ini bertujuan untuk mengetahui profil herpes zoster di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado yang meliputi jumlah kasus baru, jenis kelamin, usia, lokasi dermatom, dan terapi. Metode penelitian ialah retrospektif dengan menggunakan catatan medis pasien baru herpes zoster yang berobat di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado selama periode Januari 2011 hingga Desember 2013. Hasil penelitian memperlihatkan terdapat 96 (0,84%) kasus herpes zoster dari 11.367 pasien baru yang terdiri dari 51 (53,11%) laki-laki dan 45 (46,87%) perempuan. Kelompok usia terbanyak ialah 45-64 tahun sejumlah 59 kasus (61,46%). Lokasi dermatom tersering pada regio torakalis sinistra sejumlah 18 kasus (18,75%). Terapi yang paling sering diberikan ialah kombinasi antivirus, analgetik, roboransia, dan pengobatan topikal (bedak/cream antibiotika) sejumlah 43 kasus (44,79%).Kata kunci: herpes zoster, morbiditas